(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
The importance of protecting younger students from emergencies is enormous. Children at this age do not yet have sufficient life experience and safety knowledge. For this reason, it is very important to teach them how to behave properly during various emergencies – fire, earthquake, flood, hazards associated with electrical equipment, or other natural and man-made disasters. With the help of explanatory work, practical exercises and simulation exercises conducted at school, it is possible to form a safety culture among students. This will not only save their lives, but also serve their future development into responsible citizens in society. Therefore, emergency preparedness for primary school students should be an integral part of the educational process.